2014
DOI: 10.1016/j.peptides.2014.08.001
|View full text |Cite
|
Sign up to set email alerts
|

A tagged parathyroid hormone derivative as a carrier of antibody cargoes transported by the G protein coupled PTH1 receptor

Abstract: Based on the known fact that the parathyroid hormone (PTH) might be extended at its C-terminus with biotechnological protein cargoes, a vector directing the secretion of PTH 1-84 C-terminally fused with the antigenic epitope myc (PTH-myc) was exploited. The functional properties and potential of this analog for imaging PTH 1 R-expressing cells were examined. The PTH-myc construct was recombinantly produced as a conditioned medium (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(17 citation statements)
references
References 22 publications
0
17
0
Order By: Relevance
“…PTH exerts its effects on osteoblasts through a G-protein-coupled transmembrane receptor, PTH1R [19], by which classical two G-protein signaling cascades, i.e., the cyclic AMP-(cAMP-) and phospholipase C (PLC)-pathways are dominantly transmitted [7]. Previous studies suggested that the important target genes from the cAMP-pathway might be the c-fos, Jun, and interleukin-11 for regulating osteoblast proliferation [15,20,21].…”
Section: Introductionmentioning
confidence: 99%
“…PTH exerts its effects on osteoblasts through a G-protein-coupled transmembrane receptor, PTH1R [19], by which classical two G-protein signaling cascades, i.e., the cyclic AMP-(cAMP-) and phospholipase C (PLC)-pathways are dominantly transmitted [7]. Previous studies suggested that the important target genes from the cAMP-pathway might be the c-fos, Jun, and interleukin-11 for regulating osteoblast proliferation [15,20,21].…”
Section: Introductionmentioning
confidence: 99%
“…The myc-tagged peptide f-Nle-Leu-Phe-Nle-Tyr-Lys-myc also competed with the fluorescent probe with a potency comparable with that of f-Met-Leu-Phe ( Fig. 9 3), but the prolonged design f-Nle-Leu-Phe-Nle-Tyr-Lys-(Asn-Gly) 5 -myc, a 26-mer, was ~300-fold less potent, suggesting that the receptor discriminates against long peptides.…”
Section: Resultsmentioning
confidence: 90%
“…4) due to either the excess of free agonist in the reaction or to some steric hindrance between the agonist-bound antibody and the receptor. The prolonged peptide f-NleLeu-Phe-Nle-Tyr-Lys-(Asn-Gly) 5 -myc, while presumably maintaining its affinity for the antibodies, did not bind well enough to the FPR 1 (Fig. 3) to directly address the issue of the role of steric hindrance in the system.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations